Increasing the Detail and Realism in Web3D Distributed World - Mursid Wahyu Hananto; Ahmad Ashari; Khabib Mustofa; Agus Harjoko (Universitas Ahmad Dahlan, 2018)
A complex and detailed Web3D world which represented the physical form of an institution is very difficult to be built. To simplify the work, raster images taken from the real structure were heavily utilized. However, this method has resulted in Web3D sites which were low on detail and having minimum level of realism. To overcome this deficiency, it is proposed to maximize the use of polygons. Experiment was done by re-developing the sample world with minimum use of raster images and applying polygons to 92% parts of the site. Site elements were also distributed to three servers to cope with bottleneck problem often occured when using only one server. The result was evaluated in a series of tests to see its viewing capabilities when displayed inside the web browser against various conditions, and it also evaluated in an acceptance test carried out by site users. The majority of testers felt immensely familiar with the details shown by the model as they were able to grab a more close-to-realistic experience like a real-world walk around inside the actual building complex. Problems that often occur whe using only one server ca also be reduced by using distributed world method.